THE EFFECT OF NASAL CANNULA USE ON BLOATING INCIDENTS AT KARSA HUSADA HOSPITAL, BATU CITY - Dion Kunto Adi Patria; Riki Ristanto; Yuni Asri (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
Oxygen administration via nasal cannula at a dose of 3-4 liters/minute is standard therapy for hypoxemic patients, but it has the potential to cause bloating due to air insufflation into the gastrointestinal tract. This study analyzed the relationship between nasal cannula use at a dose of 3-4 liters/minute for >8 hours and the incidence of bloating. The study used an observational analytical study with a cross-sectional design in 30 patients who received oxygen therapy via nasal cannula at a dose of 3-4 liters/minute for >8 hours at Karsa Husada Batu Hospital. Data were analyzed using a Chi-Square Test comparing the proportion of bloating before and after the intervention. Before the intervention, no patients reported bloating. After administration of 3-4 liters/minute for >8 hours, 26 respondents (86.7%) experienced bloating. The Chi-Square test showed a significant difference (χ²=24.04; df=1; p<0.05). Conclusion: Use of a nasal cannula at a dose of 3-4 liters/minute for >8 hours significantly increases the risk of bloating.